2016
DOI: 10.1523/jneurosci.4077-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrogliopathy in Multiple Sclerosis: Low Glycolytic Metabolic Rate Promotes Oligodendrocyte Survival

Abstract: Multiple sclerosis (MS) lesions feature demyelination with limited remyelination. A distinct injury phenotype of MS lesions features dying back of oligodendrocyte (OL) terminal processes, a response that destabilizes myelin/axon interactions. This oligodendrogliopathy has been linked with local metabolic stress, similar to the penumbra of ischemic/hypoxic states. Here, we developed an in vitro oligodendrogliopathy model using human CNS-derived OLs and related this injury response to their distinct bioenergetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 39 publications
16
125
0
Order By: Relevance
“…11 In the current study, we observed a significant decrease in OCR compared to our previous report, likely reflecting an even more sustained baseline injury to the cells. The initial time point of process withdrawal without cell death was associated with a significant decrease in overall cell respiratory activity, primarily driven by a decrease in glycolytic metabolism, as we previously described.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…11 In the current study, we observed a significant decrease in OCR compared to our previous report, likely reflecting an even more sustained baseline injury to the cells. The initial time point of process withdrawal without cell death was associated with a significant decrease in overall cell respiratory activity, primarily driven by a decrease in glycolytic metabolism, as we previously described.…”
Section: Discussionsupporting
confidence: 56%
“…Our current data support the concept we proposed previously 11 that when challenged with a severe metabolic stress, OLs promote survival by sacrificing the "luxury function" 30 of macromolecular synthesis required to maintain and build myelin, instead switching to catabolic metabolism to promote cell survival. 11 Although autophagy is usually considered protective, excess is documented to be linked with cell death. 31 Makinodan et al, using OLs derived from embryonic day 16 rats, showed that process recovery could follow severing cell processes with a scalpel or inducing retraction by application of Nmethyl-D-aspartate agonist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once fortified with additional glucose, oligodendrocytes release lactate, thereby maintaining energy supplies to myelinated axons in the optic nerve. Moreover, evidence from multiple sclerosis patient tissue suggests that oligodendrocytes in low glucose conditions decrease their lactate release (Rone et al, 2016), possibly imperiling myelin maintenance but allowing cell survival. This suggests that glia are responsive to axon activity through greater release of metabolic substrate, but they have limits.…”
Section: Energy In Axonsmentioning
confidence: 99%
“…Of interest, upon exposure to hypoxic stress, mature OLs in culture demonstrated significant reduction in their energy utilization, particularly in glycolitic ATP production. This was associated with cessation of myelin production, while favoring OLs survival (58). Thus, it is possible that nonlethal chronic hypoxemia or IH-stress negatively affect mitochondrial bioenergetic function in mature, differentiating OLs and their precursors which eventuates in poor axonal myelination in premature infants.…”
Section: Postnatal Causes Of Mitochondrial Dysfunction In the Developmentioning
confidence: 99%